Using the Comfortability in Learning Scale to Enhance Positive Classroom Learning Environments - Michael Kiener; Peter Green; Kelly Ahuna (Park University, 2014)
A goal of higher education is to advance learning. This study examined the role "comfortability" plays in that process. Defined as the level of comfort students experience with their classmates, instructor, and course material, comfortability addresses how secure a student feels in the classroom. Comfortability was assessed multiple times during one semester with undergraduate students and found student comfortability significantly increased across the course of the semester and significantly predicted affective learning. These findings suggest the importance of the classroom environment in the learning process and support the need for faculty to consider "non-academic" factors in addition to course content.